Influence of factor VIII level and its inhibitor titer on the therapeutic response to corticosteroids alone in the management of acquired hemophilia: A retrospective single-center study. Issue 48 (November 2016) - Vautier, Mathieu; de Boysson, Hubert; Creveuil, Christian; Repesse, Yohan; Borel-Derlon, Annie; Troussard, Xavier; Damaj, Gandhi L.; Bienvenu, Boris; Gautier, Philippe; Aouba, Achille
Abstract : Abstract: The treatment of acquired hemophilia (AH) involves discussing whether corticosteroids should be administered alone or combined with immunosuppressant drugs, which increase the risk of infection especially in elderly patients and/or those with autoimmunity or neoplastic diseases, who represent the target population of the disease. Prognostic factors highlighting adequate responses to corticosteroids alone must be identified for satisfactory clinical response and lower infectious risk. We aimed to evaluating the efficacy of corticosteroids alone in the management of AH depending on factor VIII (FVIII, ≥ or <1 IU/dL) levels and/or inhibitor (INH, ≤ or >20 Bethesda units per milliliter [BU/mL]) titer. We conducted a retrospective single-center study including 24 patients treated for AH with corticosteroids alone. Time to achieve partial remission (PR: absence of hemorrhage and FVIII levels >50 IU/dL) was significantly shorter in the FVIII ≥ 1 IU/dL group than in the FVIII < 1 IU/dL group (20 [10–55] vs 39 [20–207] days, P  = 0.044) and in the INH ≤ 20 BU/mL and FVIII ≥ 1 IU/dL group than in the FVIII < 1 IU/dL and/or INH > 20 BU/mL group (15 [11–35] vs 41 [20–207] days, P  = 0.003). In both subgroups, time to achieve complete remission (CR: negative INH and corticosteroids below 10 mg/d) was also significantly shorter than that observed in the opposite subgroups. INH titer, considered alone, did not affect the length of time to onset of PR or CR. CR and PR rates did not differ significantly depending on these variables. Our study suggests that in AH, patients with FVIII levels ≥1 IU/dL considered alone or combined with INH titer ≤20 BU/mL could be treated by corticosteroids alone, given that this subgroup of patients displayed faster therapeutic responses to this strategy.